Encyclopedia of Life Sciences 2012
DOI: 10.1002/9780470015902.a0001709.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Speciation: Introduction

Abstract: Speciation is the formation of two or more new species from one ancestral species. How new species form is a complex process and a fundamental biological question. Answering this question provides insights into patterns of biodiversity and informs conservation strategies. Research on the causes and patterns of speciation is heavily influenced by species concepts – how we define species. The biological species concept is perhaps the most influential, and it groups individuals into species on the basis of the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In our models, we used an unsampled or “ghost” population as the source of gene flow (Excoffier et al., 2013), which simply models a reservoir for some divergent lineages now found in the sampled population (Beerli, 2004; Slatkin, 2005). It can represent a population that separated a long time ago from the sampled population, as in the case of a secondary contact after a period of isolation, like in hybrid zones at the population or species level (Alcala, Jensen, Telenti, & Vuilleumier, 2016; Alcala & Vuilleumier, 2014; Hvala & Wood, 2012; Tine et al., 2014). Such hybridization events have occurred repeatedly in human evolution (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our models, we used an unsampled or “ghost” population as the source of gene flow (Excoffier et al., 2013), which simply models a reservoir for some divergent lineages now found in the sampled population (Beerli, 2004; Slatkin, 2005). It can represent a population that separated a long time ago from the sampled population, as in the case of a secondary contact after a period of isolation, like in hybrid zones at the population or species level (Alcala, Jensen, Telenti, & Vuilleumier, 2016; Alcala & Vuilleumier, 2014; Hvala & Wood, 2012; Tine et al., 2014). Such hybridization events have occurred repeatedly in human evolution (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In our models, we used an unsampled or "ghost" population as the source of gene flow (Excoffier et al, 2013), which simply models a reservoir for some divergent lineages now found in the sampled population (Beerli, 2004;Slatkin, 2005). It can represent a population that separated a long time ago from the sampled population, as in the case of a secondary contact after a period of isolation, like in hybrid zones at the population or species level (Alcala, Jensen, Telenti, & Vuilleumier, 2016;Alcala & Vuilleumier, 2014;Hvala & Wood, 2012;Tine et al, 2014) or after long-distance dispersals between population of distinct ancestries (Fortes-Lima et al, 2018;Sedghifar, Brandvain, Ralph, & Coop, 2015;Verdu et al, 2014). Interestingly, if the source population is actually sampled, the joint SFS for the source and the target populations will reveal in the target population an excess of rare or event quite frequent derived alleles, for small and large immigration rates, respectively (Supporting Information 12), as previously reported in population or species having recently reconnected (Alcala et al, 2016;Alcala & Vuilleumier, 2014;Fraïsse et al, 2018;Tellier et al, 2011;Tine et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…the accumulation of differences between closely related populations) and speciation [9]. When the newly evolved species encountered [10][11][12], severe competition would occur owing to their high degree of similarities and thus the overlap of their niches, which could be detrimental to their survival (Gause's law [12,13]). Therefore, natural selection would favour a taxon whose species avoid spatial association, by which the severe competition would be avoided.…”
Section: Introductionmentioning
confidence: 99%